1986
DOI: 10.3109/10826088609027399
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Children of Drug Addicts

Abstract: The present study compared 70 methadone-maintained mothers (MM) and their 70 preschool-age children to a matched control group of 70 non-drug-addicted mothers (NDA) and their 70 preschool-age children on mothers' personalities, intelligence levels, and parenting attitudes and behavior; and on children's behavior and intelligence and developmental levels. Findings showed that in comparison to the control group, MM mothers performed less adaptively on measures of intelligence, personality, and parenting behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 7 publications
2
64
0
Order By: Relevance
“…The significant effect sizes were in the range of approximately 0.5 to 0.9 standard deviations. The combination of cognitive functions within the normal range but significantly worse than a non-exposed group is in accordance with previous studies of young children with prenatal opioid or poly-drug exposure (Bauman & Levine, 1986;Bunikowski et al, 1998;Hans & Jeremy, 2001;Hunt et al, 2008;Johnson et al, 1984;Logan et al, 2011;van Baar & de Graaff, 1994;Wilson, 1989;Wilson et al, 1979) and youths with such prenatal exposure (Davis & Templer, 1988;Ornoy et al, 2010).…”
Section: Cognitive Scores and Group Differencessupporting
confidence: 91%
See 1 more Smart Citation
“…The significant effect sizes were in the range of approximately 0.5 to 0.9 standard deviations. The combination of cognitive functions within the normal range but significantly worse than a non-exposed group is in accordance with previous studies of young children with prenatal opioid or poly-drug exposure (Bauman & Levine, 1986;Bunikowski et al, 1998;Hans & Jeremy, 2001;Hunt et al, 2008;Johnson et al, 1984;Logan et al, 2011;van Baar & de Graaff, 1994;Wilson, 1989;Wilson et al, 1979) and youths with such prenatal exposure (Davis & Templer, 1988;Ornoy et al, 2010).…”
Section: Cognitive Scores and Group Differencessupporting
confidence: 91%
“…Some studies find that young children who have been exposed to opioids and multiple substances have greater impairments in general cognitive abilities than non-exposed children (Bunikowski et al, 1998;Hunt et al, 2008;Johnson, Diano, & Rosen, 1984;Logan et al, 2013;Moe, 2002a;Moe & Slinning, 2001;Salo et al, 2009;van Baar & de Graaff, 1994;Wahlsten & Sarman, 2013;Wilson, 1989;Wilson, McCreary, Kean, & Baxter, 1979), whereas others do not find such differences either before (de Cubas & Field, 1993;Kaltenbach & Finnegan, 1989;Melinder et al, 2013;Rosen & Johnson, 1985;Strauss, Lessen-Firestone, Chavez, & Stryker, 1979) or after controlling for covariates (Bauman & Levine, 1986;Lifschitz, Wilson, Smith, & Desmond, 1985;Messinger et al, 2004).…”
mentioning
confidence: 99%
“…Additional reports indicate an increased incidence of respiratory insufficiency at birth (Maas et al, 1990), altered corrected QT interval on electrocardiogram during the first postnatal week (Parikh et al, 2011), postnatal hyperphagia (Martinez et al, 1999), disrupted auditory event related potentials (Paul et al, 2014), and myelination deficits (Walhovd et al, 2012). However, the prevalence of cognitive impairments produced by prenatal methadone has been questioned because some studies have not observed differences in cognitive development (de Cubas and Field, 1993;Hans, 1989;Rosen and Johnson, 1985) or performance (Bauman and Levine, 1986;Soepatmi, 1994;van Baar, 1990;van Baar and de Graaff, 1994;. These variations may be in part due to socioeconomic status and other variables (Hans, 1989).…”
Section: Methadonementioning
confidence: 99%
“…These drugs may have a negative effect on brain development, behavior, and cognition (Moe, 2002;Slinning, 2004;Walhovd et al, 2007). Several studies support the teratogenic risk model in that they link prenatal drug exposure to developmental problems, specifically problems in cognition (Baar & Graaff, 1994;Bauman & Levine, 1986;Konijnenberg & Melinder, 2014;Melinder, Konijnenberg, & Sarfi, 2013;Salo et al, 2009). However, whether the teratogenic risk model can account for behavioral problems commonly found in children of women in OMT remains to be investigated.…”
Section: Teratogenic Risk Modelmentioning
confidence: 99%